Going to school - Snowball, F. Lesley (Karachi : Paramount books, 2022)
In this book includes teacher's notes in each book includes ideas for vocabulary development, decoding strategies and a structured hierarchy of comprehension questions, to be used before during and after reading. in addition, a separate teacher's guide provides support on how to implement the guided reading approach and explains in further depth the activities and questions outlined in each book's teacher's notes.
Location: 2C
Keywords: Going to school book